2019
DOI: 10.1177/1557988319848219
|View full text |Cite|
|
Sign up to set email alerts
|

Lifestyle Factors Rather Than Helicobacter pylori Infection or Estradiol Level are Associated With Osteopenia in Japanese Men

Abstract: Although decreased calcium absorption, decreased bone formation, alcohol drinking, and smoking have been considered as causes of osteopenia in men, the cause is unknown in half of the cases. Many reports highlighted the association between Helicobacter pylori infection and osteoporosis, mainly in East Asia and Japan. To identify relevant factors of osteoporosis in men, we examined estrogen and calcium intakes and other lifestyle factors together with gastric mucosal atrophy caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Infection with H. pylori is a common risk factor for susceptibility to metabolic diseases; however, the association between H. pylori infection and BMD is limited and controversial. In most studies [ 14 21 ], no association between H. pylori infection and BMD or osteoporosis was observed, which is consistent with our observation. Recently, a meta-analysis including 1321 adults without other causes of osteoporosis or pathological bone disease at baseline showed that H. pylori infection was not associated with osteoporosis (OR = 1.49, 95% CI: 0.88 to 2.55) [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Infection with H. pylori is a common risk factor for susceptibility to metabolic diseases; however, the association between H. pylori infection and BMD is limited and controversial. In most studies [ 14 21 ], no association between H. pylori infection and BMD or osteoporosis was observed, which is consistent with our observation. Recently, a meta-analysis including 1321 adults without other causes of osteoporosis or pathological bone disease at baseline showed that H. pylori infection was not associated with osteoporosis (OR = 1.49, 95% CI: 0.88 to 2.55) [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…Atrophy of the gastric mucosa can inhibit acid secretion and thus affect calcium absorption and consequently adversely affect bone mass [ 15 ]. However, a recent cross-sectional study of 268 healthy men showed that decreased bone mineral density was not associated with H. pylori -associated estradiol levels or gastric mucosal atrophy [ 21 ]. Similarly, the chronic use of proton pump inhibitors for treatment for gastroduodenal mucosal injury may result in low levels of gastric acid, which is believed to impair calcium solubility and lead to malabsorption, thereby exacerbating bone mineral density loss secondary to hypocalcemic hyperparathyroidism, osteoclast activation, and bone resorption [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the literature evaluated regarding bone health indicators including BMD, BMC, bone mineral area (BMA), and serum metabolites in adults, eleven studies were 2-armed RCTs [ 13 14 15 16 17 18 19 20 21 22 23 ], and one was a cross-over study [ 24 ]; 5 of the studies were from the US, 2 from the United Kingdom (UK) [ 16 20 ], 2 from Australia [ 13 18 ], one from China [ 19 ], one from Japan [ 23 ], and one from Thailand [ 25 ]. Ten studies were cross-sectional [ 25 26 27 28 29 30 31 32 33 34 ], of which 7 were from Korea [ 25 27 28 29 30 32 33 ], one from Japan [ 26 ], one from Saudi Arabia [ 34 ], and one from India [ 31 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis of 21 observational studies with 9655 participants, HP infection was significantly associated with the risk of osteopenia (OR = 1.22, 95% CIs, 1.07–1.39) or osteoporosis (OR = 1.61, 95% CIs, 1.11–2.22) [ 104 ]. However, most of the studies were retrospective, cross-sectional, and did not assess anti-CagA antibodies as an indicator of infection with more virulent HP strains [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Indeed, in a preliminary analysis of a limited sample of elderly men of Caucasian ancestry, we first demonstrated that infection by HP CagA-positive strains was associated with increased cytokine levels and bone resorption markers, and was more prevalent in osteoporotic than non-osteoporotic subjects (OR = 2.13, 95% CIs, 1.02–4.44) [ 119 ].…”
Section: Gastric Disordersmentioning
confidence: 99%